North woods a novel - Mason, Daniel 1976- (Random House, 2023)
"When two young lovers abscond from a Puritan colony, little do they know that their humble cabin in the woods will become the home of an extraordinary succession of human and nonhuman characters alike. An English soldier, destined for glory, abandons the battlefields of the New World to devote himself to growing apples. A pair of spinster twins navigate war and famine, envy and desire. A crime reporter unearths an ancient mass grave--only to discover that the earth refuse to give up their secrets. A lovelorn painter, a sinister con man, a stalking panther, a lusty beetle: as the inhabitants confront the wonder and mystery around them, they begin to realize that the dark, raucous, beautiful past is very much alive."--
Keywords: Log cabins / Fiction; Puritans / Fiction; Generations / Fiction; United States / History / Fiction; New England / History / Fiction; Puritains / Romans, nouvelles, etc; Générations / Romans, nouvelles, etc; Nouvelle-Angleterre / Histoire / Romans, nouvelles, etc; Generations; Log cabins; Puritans; New England; United States; Log cabins and houses / Fiction; Forests and forestry / Fiction; Nature / Fiction; Massachusetts / Fiction; New England / Fiction; Novels; Historical fiction; Fiction; History; Romans